Peran ojek online untuk kesejahteraan masyarakat - Yuriadi Yuriadi; Desi Dwi Nur Fadilah; Mochammad Faris Ramanda; Aulia Shofiya Risa (SUKMA : Jurnal Penelitian Psikologi, 2025)
Online motorcycle taxis are a type of application-based transportation that aims to make it easier for people to carry out their daily activities. In addition, online motorcycle taxis are also considered to be cheaper and faster than other forms of transportation. The purpose of this study is to determine the role of online motorcycle taxis in improving people's welfare. The method used is qualitative with a phenomenological approach. There were three informants, and data were collected through interviews and thematic data analysis. The results obtained indicate that online motorcycle taxi driving is a flexible and easy job. Anyone can do it without having to meet many requirements and demands. Online motorcycle taxis can increase people's income and make it easier to manage work and family interests.